Assistance at mealtimes in hospital settings and rehabilitation units for older adults from the perspective of patients, families and healthcare professionals: a mixed methods systematic review protocol. (November 2015) - Edwards, Deborah; Carrier, Judith; Hopkinson, Jane
Abstract : Review question/objectives : The review question is: assistance at mealtimes for older adults in hospital settings and rehabilitation units: what goes on, what works and what do patients, families and healthcare professionals think about it? The specific objectives are: To determine the effectiveness of meal time assistance initiatives for improving nutritional intake and nutritional status for older adult patients in hospital settings and rehabilitation units To identify and explore the perceptions and experiences of older adult patients and those involved with their care with regard to assistance at mealtimes in hospital settings and rehabilitation units This mixed methods review seeks to develop an aggregated synthesis of quantitative and qualitative data on assistance at mealtimes for older adults in hospital settings and rehabilitation units in order to derive conclusions and recommendations useful for clinical practice and policy decision making. Background : Worldwide, it is estimated that between 20% and 50% of all adult patients admitted to hospital wards are malnourished.1‐4 Reported prevalence occurs, depending on the specific patient group of interest, type of healthcare setting, disease state and criteria used to assess malnutrition.1, 2, 4‐6 For older adults in hospital (over 65 years) the prevalence of malnutrition has been reported as being as high as 60%6 and can continue to deteriorate during the hospital stay.7 This is an area of concern as it is associated with prolonged hospital stays and increased morbidity (pressure ulcers, infections and falls) and mortality, especially for those with chronic conditions.4 Malnutrition in adults in developed countries is frequently associated with disease and may occur because of reduced dietary intake, malabsorption, increased nutrient losses or altered metabolic demands, with reduced dietary intake being considered the single most important aetiological factor.8 For the hospitalized older adult patient with pre‐existing malnutrition, further nutritional problems are often encountered due to a reduced dietary intake. Poor food intake for older patients in hospital may be due to the effects of acute illness, poor appetite, nausea or vomiting, "nil by mouth" orders, medication side effects, catering limitations, swallowing and/or oral problems, difficulty with vision and opening containers, the placement of food out of the patients' reach, limited access to snacks, and cultural or religious food preferences.9‐11 In the UK, national reports have shown some older patients with good appetites were not receiving sufficient nourishment because of inadequate feeding assistance.12‐14 An initial search of literature has found that this problem has also been identified in Australia, 15‐16 New Zealand, 17 Sweden, 18 and the USA.19‐20 A variety of initiatives have been developed to try to ensure that patients receive mealtime assistance if required, and include, for example: Providing meals on red trays for "at risk" patients21 ‐ this acts as a signal to staff that those patients eating from a red tray should receive support in eating their food. Protected mealtimes22 ‐ where patients are able to eat undisturbed at mealtimes and do not have any unnecessary or avoidable interruptions during this time and nursing staff are available to assist with feeding. Supervised dining rooms23 ‐ where social interaction and verbal encouragement is provided. Employment of personnel at mealtimes to assist with mealtime activities24‐25 (carers, relatives, paid employers or volunteers). Mealtime assistance has the potential to enhance nutritional intake, clinical outcomes, 26‐29 and patient experience.26, 30 Four reviews26‐29 and one scoping review31 have previously been conducted in this area. All of the reviews included adult patients over 18 years of age. The focus of the systematic review by Green et al.6 was volunteers providing feeding assistance in any institutional setting; it included a narrative analysis of 10 empirical studies from a limited number of database searches. Weekes et al.28 conducted a structured literature review focusing on improving nutritional care for patients in any healthcare setting, with specific emphasis on feeding assistance and the dining environment. The review was limited to quantitative study designs (randomized controlled trials, controlled trials and observational studies and audits). A systematic review by Wade et al.29 investigated nutritional models of care (feeding assistance, protected mealtimes, red tray initiative and communal dining) for hospitalized and rehabilitation inpatients. This review focused on data from trials only and only three databases were searched. A Joanna Briggs Institute (JBI) systematic review27 has also been published on the topic of mealtime assistance. A comprehensive search strategy was outlined and the review included six randomized controlled trials and quasi experimental designs covering a range of outcomes, but was limited to inpatients in acute care hospitals. The scoping review by Cheung et al.31 included intervention studies published from 2001 to 2012 from across three databases. The focus was on the evidence for dietary, food service and mealtime interventions in the acute care setting. In this proposed mixed methods review, the quantitative component will seek to incorporate a wider range of study designs, including but not limited to, cohort studies (with control), case‐controlled studies, descriptive and case series designs. A qualitative component will also be incorporated to help understand why initiatives do or do not work. Combining both quantitative and qualitative studies in the same review will make this the first mixed methods systematic review which considers assistance at mealtimes for older adults over 65 years of age in both hospital settings and rehabilitation units. For the purposes of this review mealtime assistance is defined as receiving help from another person to eat or complete the eating process when a meal or snack is served.32 This may include, for example, making sure that suitable cutlery is available; taking lids off food products; cutting food into smaller pieces; providing verbal encouragement; or physically feeding a patient by transferring food from the plate to the person's mouth, either at the bedside or in a separate dining room. The review will seek to investigate the feasibility, acceptability and effectiveness of initiatives for improving assistance at mealtimes for older adults in hospital settings and rehabilitation units, and will ask these questions: what goes on, what works and what do patients, families and healthcare professionals think about it?